Audience Reception of Gender Injustice in The Drama Series “Gadis Kretek” - Rahmawati, Yeni; Romadani, Anggit Tiyas Fitra; Hidayat, Rahmat (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study aims to determine the various audience receptions of gender injustice in the drama series